An electronic banking model on service quality / Noriza Mat Daud - Mat Daud, Noriza (2005)
This research deals with electronic service quality (e-service quality) which is considered as the critical factor that gives impact online retailing. There are several eservice quality dimensions which are ease of use, linkage, appearance, structure and layout, content and information, reliability, security, efficiency, communication, support and incentives. Using a sample of total 120 respondents who have experienced and did not have experienced on using online banking services, the research benchmarks the customers' perception on eleven dimensions of internet service quality. Demographic profiles have been displayed in pie chart and graph to see more precisely about customers' profile. The customers' perceptions are then being compared with the banking organizations' perception. The researcher then comes out with an electronic banking model on e-service quality. Banking organization can use this model as a guideline to focus on areas that can improve online banking service quality. Finding suggests several areas that banking organization should target for improvement. The areas include enhancing the capabilities of speed, being more sensitive with security issues, give more attention on incentives, providing the ability to translate into multiple languages, minimize the floating period for the utility payment and provide no transaction fee when customers used online banking services and many more.